Structural and electrical properties of cerium tungstate: Application to methane conversion. Issue 6 (15th April 2020) - Damascena dos Passos, Rafael Hernandez; Pereira de Souza, Carlson; Bernard-Nicod, Coline; Leroux, Christine; Arab, Madjid
Abstract: The catalytic efficiency as well as the electrical conduction mechanism of Ce2 (WO4 )3 powders synthetized for the oxidation of methane were investigated. Total and partial oxidation reactions were observed in the temperature range between 600 and 750 °C under CH4 /dry air flux, for low CH4 concentrations. The electrical conduction mechanism is based on electron tunneling at low temperature (<650 °C) and hopping over an ion barrier at high temperature, which favors the catalytic oxidation of CH4 in air; these mechanisms occur during the partial and total oxidation under weak gas flow. The occurrence of these types of conduction mechanism was related both to the distorted monoclinic structure of Ce2 (WO4 )3 and to the larger structural cavities, as evidenced respectively by X-ray diffraction analyses (Rietveld analyses) and high-resolution transmission electron microscopy. The oxidation state of cerium is 3 + in the compound, as revealed by XPS investigations.